FE based simulation and experimental validation of forces in dry turning of aluminium 7075. (2020) - Mali, Rahul A.; Agrahari, Mata Dayal; Gupta, T.V.K.
Abstract: This work is mainly focused on validation of simulated cutting forces obtained from a finite element based Deform-3D software in dry turning of Aluminium 7075 alloy with the experimental results. Experimental runs are performed to investigate the effect of cutting parameters like speed, feed, and depth of cut on both the cutting and feed forces in turning of Al-7075, which is widely used in automobile components and aircraft structures. A multiple regression analysis, i.e., ANOVA is used to determine the correlation between the cutting parameters and the machining forces. This study establishes the relevance and suitability of Deform-3D simulation software to estimate the forces in turning process. Hence, the simulation-based approach can be used successfully to predict the performance characteristics of the machining process reducing the experimental efforts at the shop floor. Further, this work has revealed a scope to validate the other machining responses, i.e., the tool wear, chip morphology, and residual stresses, etc. in machining with Deform-3D and also to compare the obtained results with other finite element based software tools.